2021
DOI: 10.1039/d1cp00194a
|View full text |Cite
|
Sign up to set email alerts
|

Role of free volumes and segmental dynamics on ion conductivity of PEO/LiTFSI solid polymer electrolytes filled with SiO2 nanoparticles: a positron annihilation and broadband dielectric spectroscopy study

Abstract: Limited ionic conductivity of polymer electrolytes is a major issue in their industrial application. Enhancement in ionic conductivity in Poly (ethylene oxide), PEO, based electrolyte have been achieved by loading...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…We have also prepared an electrolyte with the linear PEO only to compare with the blends. The neat PEO/LiTFSI resulted in an ionic conductivity of ∼10 –3 S/cm at 60 °C, which is in agreement with previously reported results. ,,,, In the case of the blend electrolytes, the ionic conductivity for blends with the linear PEO decreased about an order of magnitude, as expected due to its slower segment dynamics in the presence of PMMA . More importantly, we found that the temperature dependence of ionic conductivity for the PEO/PMMA blend electrolytes using different PEO topologies well fit the VFT model well over the temperature range studied, suggesting that Li ion transfer is mainly correlated to the segmental dynamics.…”
Section: Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We have also prepared an electrolyte with the linear PEO only to compare with the blends. The neat PEO/LiTFSI resulted in an ionic conductivity of ∼10 –3 S/cm at 60 °C, which is in agreement with previously reported results. ,,,, In the case of the blend electrolytes, the ionic conductivity for blends with the linear PEO decreased about an order of magnitude, as expected due to its slower segment dynamics in the presence of PMMA . More importantly, we found that the temperature dependence of ionic conductivity for the PEO/PMMA blend electrolytes using different PEO topologies well fit the VFT model well over the temperature range studied, suggesting that Li ion transfer is mainly correlated to the segmental dynamics.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Also, the effect of free volume, which results from the free spaces between monomers along the (same or different) polymer chains, on ionic conductivity was investigated by various studies in PEO-based SPEs. ,,, The increase in free volume in the polymer matrix resulted in assisted ion migration, enhancing the ionic conductivity in these SPEs. Recent studies confirmed that the hampered crystallization of PEO due to the addition of nanofillers or other polymers could increase the free volume. , Furthermore, it is known that an increasing number of branches in the nonlinear topologies resulted in a decrease in crystallization, increasing free volume. , The ion migration within SPEs, known as the hopping mechanism, is well established, in which the available free volume helps lithium ions to transport through hopping provided by the polymer segmental motions. ,,, In this manner, Utpalla et al investigated the role of free volume and segmental dynamics on the ion conductivity of PEO-based SPEs and found that the increase in free volume with the addition of inorganic nanofillers enhances the free volume fraction and decreases the crystallinity of pure PEO by increasing free available spaces between polymer chains, thus promoting the ionic conductivity. Similarly, Michael et al reported that the polymer chains leaning to coil up around nanofillers added into PEO paved the way for the transportation of Li + ions by providing the additional free volume as a result of decreasing crystallization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The free volumes are the unoccupied spaces that exist within the amorphous domains of a polymer . The focus of this work is to characterize the free volumes in needleless electrospun polymer nanofibers in terms of their size, number, and distribution using the popular free volume probe “positronium annihilation lifetime spectroscopy” technique. ,,, A recent thermal study on polymer nanofibers reveals that their glass-transition temperature is size dependent. , Thus, it is also of interest to understand how the free volumes of nanofibers are related to their T g . The conventional differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA) are used for T g measurements.…”
Section: Introductionmentioning
confidence: 99%
“…28 The focus of this work is to characterize the free volumes in needleless electrospun polymer nanofibers in terms of their size, number, and distribution using the popular free volume probe "positronium annihilation lifetime spectroscopy" technique. 28,32,48,49 A recent thermal study on polymer nanofibers reveals that their glass-transition temperature is size dependent. 6,18 Thus, it is also of interest to understand how the free volumes of nanofibers are related to their T g .…”
Section: Introductionmentioning
confidence: 99%